Seismic Behavior of Reinforced Concrete Frame Joints in Coastal Atmosphere - Chen Cao; Shan-suo Zheng; Wei-bing Hu; Li-guo Dong; Xiao-rui Liu (Advances in Civil Engineering)
The study aims to research the influence of salt fog corrosion cycles on seismic performance of reinforced concrete (RC) frame beam-column joints in coastal atmosphere. Based on low cyclic loading tests of six RC frame beam-column joint specimens, this study analyses the failure patterns, hysteresis loops, load carrying capacity, displacement, backbone curves, and energy dissipation capacity of corrosion-damaged RC frame beam-column joints. The effect of salt fog corrosion cycles and axial compression ratios are tested repeatedly. The results show that with the same level of axial compression of the frame joint specimens, as the increase of salt fog cycles, the strength, ductility, energy dissipation, bearing capacity, and deformation capacity of joints degenerated to different degrees． When the corrosion level is the same, the stiffness degradation appeared to be more apparent as the increase of axial compression ratio. Then, the behavior degeneration rule of the RC frame beam-column joints is analyzed and formed according to the results of the test; the degeneration restoring force models of corroded RC frame beam-column joints is formed and verified based on Clough’s three-line degenerate restoring force model and the introduction to cyclic degeneration index. The results show that the restoring force model can better describe the hysteresis characteristics of the beam-column joints of corroded RC frames. The research is a theoretical reference for the seismic analysis of the RC frame structure affected by coastal atmospheric environment.